Optimal growth (classic, Re=2000,A=1,Wo=15): time series for selected t0 - Duo Xu; Baofang Song; Marc Avila (PANGAEA, 2022)
The data are obtained via an in-house Matlab script (developed by Dr. Baofang Song) to compute the non-modal transient growth of disturbances in pulsatile and oscillatory pipe flows. In this study, a Newtonian fluid driven by pulsatile and oscillatory flow rate flows in a straight pipe. In pulsatile flow, there are three governing parameters: steady Reynolds number (defined by the steady flow component), pulsation amplitude (ratio of oscillatory and steady flow component) and Womersley number (dimensionless pulsation and oscillation frequency). In oscillatory flow, due to vanishment of steady flow component, oscillatory Reynolds number (defined by the oscillation flow component) and Womersley number. The Reynolds number defined by the thickness of Stokes layer is alternatively used for the oscillatory Reynolds number. The study was carried out in a manner that one governing parameter varies while other governing parameters are fixed. The data file extquotesingletime_TG_all.dat extquotesingle shows the maximum energy amplification over all modes at each time instant. This file includes three columns: the first column indicates dimensionless time; the second column indicates the time normalized by the pulsation period; the third column indicates the energy amplification at a time instant (first column).